Anthropogenic Attribution of the Increasing Seasonal Amplitude in Surface Ocean pCO2 - Fortunat Joos; Angélique Hameau; Thomas L. Frölicher; David B. Stephenson (Geophysical Research Letters, 2023)
Abstract A positive trend in time has been noted in the seasonal amplitude of surface ocean pCO2 over much of the oceans, which is expected to have detrimental impacts on marine ecosystems. To determine whether or not this has an anthropogenic cause, this study investigates historical climate simulations from the Detection and Attribution Model Intercomparison Project with and without anthropogenic forcing. The simulations with anthropogenic forcing show clear evidence of positive trends, whereas the simulations with constant preindustrial atmospheric CO2 and natural external forcing give only negligible trends. A statistical analysis of five zonal latitudinal bands reveals that the trends detected over 1990–2014 in an ensemble of six observational products are attributable to anthropogenic forcing in mid‐latitudes (40°N–10°N, 10°S–40°S), while no trends are detected and modeled in the tropics and the Southern Ocean. Most models fail to represent the sign of the observed climatological mean seasonal cycle difference in high latitudes.